The museum and its usages in two Balkan novels: Elif Shafak`s Black milk and Dubravka Ugrešić`s The museum of unconditional surrender (Colloquia Comparativa Litterarum, 2025)
This article examines the possible concept of the museum in literature – a ‘museum’ not only like a metaphor but also like a specific type of novel. This is an attempt to trace the possible meetings (or usages) of two Balkan novels – Dubravka Ugrešić`s historical museum and Elif Shafak’s literary harem. The focus of the study is on the never-ending quest and the search for human multifacetedness and human completeness.In her autobiographical novel Black Milk: On Writing, Motherhood and the Harem Within Elif Shafak is trying to ‘arrange’ her own literary museum. She was able to gather in her ‘collection’ women writers like Zelda Fitzgerald, Sylvia Plath, Sevgi Soysal, Halide Edib, Ayn Rand, etc. In The Museum of Unconditional Surrender Dubravka Ugrešić was able to collect, preserve and show (without apparent connection between them) the fragments/photographs/books of her own biography as a kind of ‘museum’ novel.
Keywords: museum; collection; inventory book; album; Balkan novels; women writers; Elif Shafak; Dubravka Ugrešić